Desenvolvimento e validação de método analítico para determinação de benzoato, sorbato, metil e propilparabenos em produtos alimentícios utilizando a eletroforese capilar - Petruci, João Flávio da Silveira [UNESP]; Cardoso, Arnaldo Alves [UNESP]; Pereira, Elisabete Alves (Sociedade Brasileira de Química, 2011)
In this work, a rapid and simple method using capillary electrophoresis (CE) was developed for the determination of the benzoate, sorbate, methyl and propylparaben in foodstuffs. A running buffer consisting of 20 mmol L-1 (pH = 9.3) tetraborate enabled separation of the analytes in less than 5 min. The detector wavelength was set at 220 nm. The method was successfully applied to the analysis of sodas, sweeteners, sauces and juices. The range of preservatives found were from 478.5-466.6 mg kg-1 for methylparaben , 83.7-231.3 mg kg-1 for sorbate and 336.7-428.3 mg kg-1 for benzoate.
Development and validation of analytical method to determination of benzoate, sorbate, methyl and propylparaben in foodstuffs by capillary electrophoresis
Keywords: food analysis; preservatives; capillary electrophoresis